METHODS FOR DETERMINING THE NATURAL TIME COURSE OF IMMUNE RESPONSE AND MODIFYING INTRACELLULAR PH FOR DISEASE CONTROL - ZENG, Wei-Ping (2025)
This invention provides methods to determine the stage in the natural time course of immune response in a subject. It describes method to control immune response by targeting regulatory mechanisms differentially operating in lymphocytes at different stages in the natural time course of immune response. One kind of such regulatory mechanism is the mechanisms of energy metabolism that control intracellular pH (pHi), which in turn control cell death and proliferation. This invention also describes a combinatorial approach to lowering pHi of neoplastic cells to induce their death using compositions of combinations of regulators of energy metabolism. Finally, this invention provides methods to treat skin or mucosa infections or neoplasia by topical application of pH modifier(s) that lower pH.